The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/s11663-998-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the reduction process of iron ore particles in two stages of twin-fluidized beds connected in series

Abstract: A mathematical model is presented to describe the reduction process of iron ore particles in two stages of twin-fluidized beds (TFBs) connected in series: prereduction and final reduction stages. Main features of the model are the inclusion of particle degradation phenomenon to account for its effect on reduction of iron oxides and reduction kinetics for multiparticles having a wide size distribution. It was found that about 90 pct of overall particle degradation occurs in the prereduction stage mainly due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…26) Hence, it is reasonable to assume that the mass transfer resistance of gases from the bulk to the particles surface is not significant. As very fine particles have been used in both TG as well as FB, diffusion through the porous reacted shell is also not expected to be significant.…”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…26) Hence, it is reasonable to assume that the mass transfer resistance of gases from the bulk to the particles surface is not significant. As very fine particles have been used in both TG as well as FB, diffusion through the porous reacted shell is also not expected to be significant.…”
Section: Modelingmentioning
confidence: 99%
“…27) On the other hand, the solid particles in the bed move in all random directions and hence can be considered to be in a perfectly stirred condition. 13,26,27) It is also well-known that the vigorous motion of the solid particles in a fluidized bed will ensure the temperature equalization along the bed. The isothermal character within the bed is one of the most characteristic properties of the fluidized bed reactor.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…And it has been observed in practice especially for fine iron oxide particles. [18][19][20][21] Hence, it is assumed that the mass transfer resistance of gases from the bulk to the surface can be neglected. Thurnhofer 18) conducted microscopical analyses of polished sections of reduced iron ore fines and observed that a high amount of pores were spread through the entire fine.…”
Section: )mentioning
confidence: 99%
“…So pore diffusion is not limiting the reduction. Based on these assumptions and observations, Hahn,19,20) Thurnhofer,…”
Section: )mentioning
confidence: 99%